Neomacrodione: a new degraded diterpenoid from the roots of Neoboutonia macrocalyx Beng (Euphorbiaceae). Issue 1 (2nd January 2018) - Maffo, Timoleon; Melong, Raduis; Nganteng, Dieu Ne Dort; Wafo, Pascal; Ali, Muhammad Shaiq; Ngadjui, Bonaventure Tchaleu
Abstract: One new degraded diterpenoid 3, 6-dihydroxy-1, 7-dimethyl-9, 10-phenantroquinone (neomacrodione) (1 ) together seven known compounds were isolated from the roots of Neoboutonia macrocalyx (Euphorbiaceae). The structures of the compounds were established based on their NMR and mass spectrometric data in conjunction with those previously reported in the literature. Compound (1 ) displayed moderate antibacterial activities. Abstract :